Innovation in evaluation to inform policy convergence: Complex systems approach to assess entrepreneurship-driven intervention in eKutir’s VeggieKart - Moore, Spencer; Jha, Srivardhini K.; Mishra, Suvankar; Ross, Daniel; Allen, Summer L.; Dubé, Laurette (Daya Publishing House, 2015)
Innovation in evaluation to inform policy convergence: Complex systems approach to assess entrepreneurship-driven intervention in eKutir’s VeggieKart